2014
DOI: 10.1371/journal.pone.0103999
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Activities of Extracts from Cassia alata, Eleusine indica, Eremomastax speciosa, Carica papaya and Polyscias fulva Medicinal Plants Collected in Cameroon

Abstract: BackgroundThe vast majority of the population around the world has always used medicinal plants as first source of health care to fight infectious and non infectious diseases. Most of these medicinal plants may have scientific evidence to be considered in general practice.ObjectiveThe aim of this work was to investigate the antioxidant capacities and anti-inflammatory activities of ethanol extracts of leaves of Cassia alata, Eleusine indica, Carica papaya, Eremomastax speciosa and the stem bark of Polyscias fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 44 publications
6
65
0
Order By: Relevance
“…C.alata used as a traditional medicine, particularly valued for its laxative effect and DOI: http://dx.doi.org/10.22192/ijarbs.2017.04.12.012 its effective treatment of several skin conditions, including ringworm and scabies [4,5]. Crude leaf extracts have shown antibacterial activity against a range of bacteria and also antitumor activity [6]. The bark is used to treat skin diseases, diarrhoea, worms, parasitic skin diseases, scabies and eczema [7].…”
Section: Introductionmentioning
confidence: 99%
“…C.alata used as a traditional medicine, particularly valued for its laxative effect and DOI: http://dx.doi.org/10.22192/ijarbs.2017.04.12.012 its effective treatment of several skin conditions, including ringworm and scabies [4,5]. Crude leaf extracts have shown antibacterial activity against a range of bacteria and also antitumor activity [6]. The bark is used to treat skin diseases, diarrhoea, worms, parasitic skin diseases, scabies and eczema [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has numerous pharmacological activities such as antitumor [10], anthelmintic [11], anti-bacterial [12], anti-oxidant and antiinflammatory [13], and anti-diabetic activities [14]. A recent study found that S. alata (250 and 500 mg/kg) improved abnormal lipid metabolism by suppressing hepatic lipogenic genes, sterol regulatory element binding protein 1c (SREBP1c), fatty acid synthase (FAS) and acetyl-CoA carboxylase (ACC) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative damage of tissues and biomolecules occur when the levels of free radicals species exceed the level of antioxidant mechanism eventually leading to disease conditions [30]. Medicinal properties of plants have been investigated for their potential antioxidant activities to counteract metabolic disorders [31], Plant extracts and plant-derived antioxidant compounds may potentiate the body's antioxidant defense mechanisms [32]. From results, it may be postulated that Parmelia was able to reduce the stable free radical DPPH to the yellow-colored diphenylpicrylhydrazine exhibiting free radical scavenging activity.…”
Section: Discussionmentioning
confidence: 99%